The Butcher, Vintner, and Cidermaker: Crafting Good Food in Contemporary America - Jones, Brad (Cuizine)

(untitled) (McGill University Library, 2015)
We are experiencing a contemporary “renaissance” of craft food production in America. Although recent scholarship has highlighted the marketing and consumption of artisanal foods as socially, culturally, and economically interesting, fewer scholars focus on artisanal production. Amidst the relative paucity of academic interest, anthropologist Heather Paxson has persuasively argued that American artisan cheese gains status as an object good to make in the same way that it achieves its distinction as an object good to eat. My investigations elaborate on this claim to show that the complex variables motivating artisanal cheese production extend, alongside if not neatly parallel, to other American artisan food domains as well. I argue that it is the moral component of making in which artisans simultaneously craft “good” products and themselves as “good” producers that gives meaning and value to the quotidian aspects of their daily lives. Employing an ethnographic approach that juxtaposes three diverse artisan food producers—a butcher, vintner, and cidermaker— I show that artisans are imbued with a vital sense of agency and are motivated by the belief that their labour and their lives are employed in the production of not only material objects but a better world. In better understanding the motivations of craft food production, we learn that the meaning and constitution of the “good life” can be realized in myriad ways and, more narrowly, to appreciate that sentimental factors buttress socio-economic behaviour as much as the predominant logic of neoliberalism.